Conserved effectors underpin the virulence of liverwort-isolated Pseudomonas in divergent plants - Robinson, Kayla; Buric, Lucia; Grenz, Kristina; Chia, Khong-Sam; Hulin, Michelle T; Ma, Wenbo; Carella, Philip (Current biology, 2025)
Plant pathogenic Pseudomonas species naturally antagonize a diverse range of flowering plants. While emerging research demonstrates that isolates belonging to the P. syringae species complex colonize diverse hosts, the extent to which these bacteria naturally infect non-flowering plants like the model liverwort Marchantia polymorpha remains unclear. Here, we identify natural associations between Pseudomonas viridiflava and the liverwort Marchantia polymorpha. Pseudomonas bacteria isolated from diseased liverworts in the wild successfully re-infected M. polymorpha under pure culture conditions, producing high in planta bacterial densities and causing prominent tissue maceration. Comparative genomic analysis of Marchantia-associated P. viridiflava identified core virulence machinery like the type III secretion system (T3SS) and conserved effectors (AvrE and HopM1) that were essential for liverwort infection. Disease assays performed in Nicotiana benthamiana further confirmed that liverwort-associated P. viridiflava infect flowering plants in an effector-dependent manner. Our work highlights P. viridiflava as an effective broad host pathogen that relies on conserved virulence factors to manipulate evolutionarily divergent host plants.